Characteristics of the fecal microbiome and metabolome in older patients with heart failure and sarcopenia - Peng, Jieting; Gong, Hui; Lyu, Xing; Liu, Yang; Li, Shizhen; Tan, Shengyu; Dong, Lini; Zhang, Xiangyu (Frontiers in Cellular and Infection Microbiology, 2023)
Increasing evidence supports that gut microbiota plays an important role in the development of cardiovascular diseases. The prevalence of sarcopenia is increasing in patients with heart failure. Muscle wasting is an independent predictor of death in heart failure patients. In this study, we aimed to explore the characteristics of intestinal bacteria and metabolites in heart failure patients with or without sarcopenia. Fecal samples of 33 heart failure patients without sarcopenia, 29 heart failure patients with sarcopenia, and 15 controls were collected. The intestinal microbiota was analyzed using 16S rRNA sequencing and the metabolites were detected using the gas chromatography-mass spectrometry method. There were significant differences in the overall microbial community structure and diversity between control and heart failure patients with or without sarcopenia. However, no clear clustering of samples was observed in heart failure with and without sarcopenia patients. Several bacterial, particularly Nocardiaceae, Pseudonocardiaceae, Alphaproteobacteria, and Slackia were significantly enriched in the heart failure patients without sarcopenia, while Synergistetes was more abundant in the heart failure patients with sarcopenia. Isobutyric acid, isovaleric acid, and valeric acid were lower in heart failure patients with sarcopenia than that without sarcopenia but lacked significance. This study demonstrated that there are differences in the gut microbiota and metabolites among control individuals, and heart failure patients with and without sarcopenia. Modulating the gut microbiota, especially Short-chain fatty acids-producing bacteria could be a new target for the prevention and treatment of sarcopenia in heart failure patients.